Epidemiological Profile of Illnesses in Older Adults Treated at the Regional Emergency Service of Cienfuegos - Lázaro Armando Águila Trujillo; Lourdes Elena Duany Badell; Vivian Isabel Chávez Pérez; Yoleysi Arteaga Cuellar; Midalys del Carmen LLanes Cartaya; Juan Rafael Zerquera Rodríguez (Revista Finlay)
Foundation: population aging represents a challenge for Emergency Services that have to face an increase in care pressure. Objective: to describe the epidemiological profile of the conditions in older adults treated in the Regional Emergency Service of the Cienfuegos municipality during the year 2022. Method: a descriptive and cross-sectional study was carried out. The universe was made up of 7748 patients, 51.0 % corresponded to the Cienfuegos municipality represented by 3917 patients. The variables analyzed were: age, sex, reason for call, response time to the request, final diagnosis, need for hospital admission and deaths during the journey. Absolute numbers and percentages were used from descriptive statistics and the standard deviation was used to know the variability of the variable. Results: older adults aged 60 to 64 years predominated, which represented 39.2 %; falls corresponded to 41.7 %; followed by calls made using vulgar language, which represented 28.7 %; 67.5 % were attended in less than 10 minutes; only 21.5 % of the elderly died during the journey; the need for hospital admission was represented by 76.5 %; the highest reports were due to high blood pressure and stroke. Depending on sex, women continue to make a difference. Conclusions: older adults aged 60 to 64 years and women predominated in the study. Falls and calls made due to abusive language were more prevalent. Patients were seen in less than 10 minutes. Only 21.5 % of the elderly died during the journey. The highest reports were due to high blood pressure and stroke.